Evaluating the global, regional, and national burden of congenital heart disease in infants younger than 1 year: a 1990–2021 systematic analysis for the GBD study 2021 - Deng, Lili; Li, Qinhong; Cheng, Zugen (Frontiers in Pediatrics, 2025)
BackgroundPrevious estimates of congenital heart disease (CHD) have been constrained by limited data sources, narrow geographic focus, and a lack of specific assessment of infants younger than 1 year. As part of the Global Burden of Diseases (GBD), Injuries, and Risk Factors Study 2021, this research provides comprehensive estimates of mortality, prevalence, and disability attributable to CHD in infants under 1 year. The study encompasses data from 204 countries and territories, covering the period from 1990 to 2021.MethodsThis cross-sectional analysis utilized data from the 2021 GBD study, encompassing 204 countries and territories. The study focused on infants under 1 year of age with CHD. The GBD dataset was accessed on June 10, 2024.Main outcome measuresThe primary outcomes included prevalence, all-cause, and cause-specific mortality, disability-adjusted life years (DALYs), and the corresponding estimated annual percentage changes (EAPCs). Trends were stratified by region, country, age, and Sociodemographic Index (SDI).ResultsIn 2021, CHD resulted in 250,811.32 deaths globally [95% uncertainty interval (UI), 207,821.56–304,084.49], representing a 52.58% decrease from 1990. Among these, 167,985.02 deaths (95% UI, 138,221.77–208,321.59) occurred in infants younger than 1 year. In infants under 1 year old, the 1990 mortality rate for CHD ranked behind neonatal encephalopathy due to birth asphyxia and trauma, diarrheal diseases, neonatal preterm birth, and lower respiratory infections. By 2021, its mortality rates had decreased to the eighth leading cause of death.InterpretationCHD remains a significant and rapidly escalating global challenge in child health. While it is difficult to significantly reduce the prevalence of CHD, especially in complex cases, advances in prenatal diagnosis and the availability of medical termination of pregnancy in certain regions have led to demographic changes. Additionally, birth rates, typically lower in high-SDI countries, also influence the prevalence of CHD. Given these factors, the focus should be on improving survival outcomes and quality of life for affected infants. Our findings reveal substantial global disparities in prevalence among infants under 1 year, emphasizing the need for policy reforms that address screening, treatment, and data collection to mitigate these disparities.